1990
DOI: 10.1161/01.cir.81.1.58
|View full text |Cite
|
Sign up to set email alerts
|

In vivo quantitative ultrasonic evaluation of myocardial fibrosis in humans.

Abstract: The aim of this study was This approach, based on the time domain analysis of the radiofrequency signals, appears promising as a means to establish certain aspects of ultrasonic diagnosis on a more quantitative basis.3,4 The assessment of regional myocardial fibrosis would be of particular interest since excessive myocardial fibrosis is both an important sign and is associated with a variety of myocardial diseases.Even though there were substantial problems in comparing exactly the anatomic region interrogat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
136
1
1

Year Published

2002
2002
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 214 publications
(143 citation statements)
references
References 18 publications
5
136
1
1
Order By: Relevance
“…In experimental studies, IBS absolute values have been shown to be reliable indices of LV fibrosis. In addition, they have been shown to reflect myocardial collagen content as assessed by endomyocardial biopsy in humans (15,16,18). It has been demonstrated that even mild reductions in renal function are associated with a greater prevalence of LVH (27,28); the increase in IBS reflectivity that was observed in our study also indicates an early increase in LV collagen deposition, beginning well before the development of ESRD.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…In experimental studies, IBS absolute values have been shown to be reliable indices of LV fibrosis. In addition, they have been shown to reflect myocardial collagen content as assessed by endomyocardial biopsy in humans (15,16,18). It has been demonstrated that even mild reductions in renal function are associated with a greater prevalence of LVH (27,28); the increase in IBS reflectivity that was observed in our study also indicates an early increase in LV collagen deposition, beginning well before the development of ESRD.…”
Section: Discussionsupporting
confidence: 63%
“…Experimental studies have suggested that integrated backscatter (IBS) measures may be related to myocardial collagen content (11)(12)(13)(14). In humans, ultrasonic backscatter indices have been shown to be related to myocardial collagen content as assessed by endomyocardial biopsy (15)(16)(17)(18). Therefore, we considered it worthwhile to analyze myocardial ultrasonic backscatter (IBS) in patients who had CRF and were undergoing hemodialysis, in patients with mild to moderate CRF, and in patients with essential hypertension with comparable age, BP values and LVM to evaluate whether interstitial collagen deposition as evaluated by acoustic densitometry may appear early in the course of chronic kidney disease (CKD).…”
mentioning
confidence: 99%
“…The extracellular matrix represents an important source of myocardial IBS, 14 and several experimental studies have demonstrated that IBS in diastole correlates with the collagen content within the myocardium. 15,16 Therefore, the acoustic densitometry technique can noninvasively provide a relative estimate of myocardial fibrosis. The standardized IBS and cyclic variation of IBS data were significantly improved in SHRs treated with rosiglitazone when compared with SHRs treated with saline.…”
Section: Discussionmentioning
confidence: 99%
“…Heart tissue characterization by means of echocardiography via the integrated backscatter (IBS) technique was also performed in a subset of cirrhotic patients in an attempt to obtain information on myocardial texture to assess whether hypertrophy or fibrosis is the background morphological change. This technique allows to obtain an indirect estimate of tissue density, usually decreased when a higher percentage of muscle fibres is present and increased when fibrosis prevails [36,37]. We also obtained information on the effects of aging on the morphofunctional heart changes observed.…”
Section: Introductionmentioning
confidence: 99%